Do corporate social responsibility and technological innovation get along? A systematic review and future research agenda - Hailan Yang; Xiangjiao Shi; Muhammad Yaseen Bhutto; Myriam Ertz (Journal of Innovation & Knowledge (JIK), 2024)
Corporate social responsibility (CSR) and technological innovation (TI) are two fundamental driving forces for sustainable development. The importance of the CSR-TI relationship has grown in prominence over recent years. This study is motivated by two research questions: (1) What makes the CSR-TI relationship conclusions different? (2) Which emerging themes in the literature will likely set the stage for future work? Using VOSviewer for co-occurrence analysis, this research examines 67 scholarly works in related research fields from 1996 to 2023 in 36 leading journals to answer these questions. This paper is a systematic literature review of the CSR-TI relationship from different perspectives. Addressing these two research questions helps us clarify the internal logic of the existing research in the CSR-TI relationship, deepens the understanding of the relationship between CSR and TI, and provides a glimpse of the future.
Keywords: 650; Corporate social responsibility; Technological innovation; Sustainable development; Stakeholders; Systematic literature review; Future research agenda